2011
DOI: 10.1002/pon.2027
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and mental health in the bereaved family members of patients with terminal cancer

Abstract: Our results confirm that bereaved family members of patients with cancer have lower health-related QOL and mental health than the general population. Healthcare providers should focus more attention on this vulnerable group, and various support programs should be developed to improve their health-related QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 42 publications
3
63
1
7
Order By: Relevance
“…For instance, Song et al . found that longer duration of survival after palliative care referral was negatively correlated with health‐related QOL in bereaved relatives of cancer patients.…”
Section: Resultsmentioning
confidence: 95%
“…For instance, Song et al . found that longer duration of survival after palliative care referral was negatively correlated with health‐related QOL in bereaved relatives of cancer patients.…”
Section: Resultsmentioning
confidence: 95%
“…Unmarried men were excluded from the final sample due to their low numbers and because of prior research suggesting worse bereavement outcomes in spouses than other adult family caregivers. 29 All analyses were performed using SAS V.9.3 (SAS Institute, Inc, Cary, North Carolina, USA). All p values were derived from two-sided statistical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Se analizaron los artículos de acuerdo al esquema de clasificación de los niveles de evidencia y fuerza de la recomendación de Shekelle et al (25) . Cada uno de los artículos fue revisado individualmente por pares con el objetivo de identificar los niveles de evidencia, instrumentos y/o intervención, diagnóstico de los pacientes cuidados y nivel de recomendación (ver el cuadro 1).…”
Section: Procedimiento De Evaluación De La Evidenciaunclassified